Performance, good taste, and knowledge in doctoral education: an analysis of confessional narrative in San Luis Potosí, Mexico (Revista Innova Educación, 2024)
The study of the conditions and complexities of postgraduate programs is a strategy that contributes to the understanding, development, and continuity of educational offerings in higher education institutions. The postgraduate experience, through narrative, is a symbolic construction that is shaped by knowledge and politics. This performance weaves the fabric of academic good taste as a distinctive feature that legitimizes its graduates. This research is a qualitative-inductive case study that uses the categories of performance, habitus, and experience to outline, from the narrative of graduates of a regional Doctorate in Educational Development program, the symbolic space in education to understand its contribution. The confessional narrative technique is used to obtain discursive portions, processed in a matrix and analyzed with QDA Miner 1.4. The results allow constructing the argument that the doctoral program is a stage that graduates endure, caught between meeting academic expectations and their education. A part of the doctoral student's academic life is dedicated to assimilating academic good taste, a mechanism that enables the reproduction of cultural capital in this space. In this sense, the doctoral program is critical in its didactic strategies and content management in its seminars, but students are not trained to question the set of habituations inherited from the program until they gain an outside perspective. The doctorate shapes its heirs, and after enduring it, transformation is possible.
Keywords: academic performance; behavior; education; knowledge; transformation